![\text {Mass of earth =} 5.97 \times 10^{24} \text { kg}](https://tex.z-dn.net/?f=%5Ctext%20%7BMass%20of%20earth%20%3D%7D%205.97%20%5Ctimes%2010%5E%7B24%7D%20%5Ctext%20%7B%20kg%7D)
![\text {Mass of Venus =} 4.87 \times 10^{24} \text { kg}](https://tex.z-dn.net/?f=%5Ctext%20%7BMass%20of%20Venus%20%3D%7D%204.87%20%5Ctimes%2010%5E%7B24%7D%20%5Ctext%20%7B%20kg%7D)
![\text {Difference = }5.97 \times 10^{24} - 4.87 \times 10^{24}](https://tex.z-dn.net/?f=%5Ctext%20%7BDifference%20%3D%20%7D5.97%20%5Ctimes%2010%5E%7B24%7D%20%20-%204.87%20%5Ctimes%2010%5E%7B24%7D)
![\text {Difference = }(5.97 - 4.87) \times 10^{24}](https://tex.z-dn.net/?f=%5Ctext%20%7BDifference%20%3D%20%7D%285.97%20-%204.87%29%20%5Ctimes%2010%5E%7B24%7D%20)
![\text {Difference = }1.1 \times 10^{24} \text { kg}](https://tex.z-dn.net/?f=%5Ctext%20%7BDifference%20%3D%20%7D1.1%20%5Ctimes%2010%5E%7B24%7D%20%5Ctext%20%7B%20kg%7D)
--------------- In Pure Text Format --------------
Mass of the earth = 5.97 x 10^{24}
Mass of Venus = 4.87 x 10^{24}
Difference = (5.97 - 4.87) x 10^{24} = 1.1 x 10^{24} kg
Answer:
To find out the first three terms of 3n - 2 substitute 1 ,2 and 3 into the equation.
so the three terms a
3(1)-2=1
3(2)-2=6-2=4
3(3)-2=9-2=7
As you can see the sequence goes up in 1,4 and 7.To find out the 10th term you also substitute 10 into the equation so 3(9)-2=18-2=16
so 16 is the tenth term
Hope this helped!
Answer:
2 x 10 ^ 6
Step-by-step explanation:
I’m sure that the answer is x=3
Answer:
can you get a better picture it is hard to see
Step-by-step explanation: